GJG-9: A high yielding and stem rot tolerant Spanish bunch groundnut (Arachis hypogaea L.) variety for Gujarat state: GJG-9: A HIGH YIELDING AND STEM ROT TOLERANT SPANISH BUNCH GROUNDNUT VARIETY - K L DOBARIYA; J H VACHHANI; L L JIVANI; V H KACHHADIA; H G SHEKHAT (Journal of Oilseeds Research, 2014)
A Spanish bunch groundnut genotype GJG-9 was identified based on the mean pod yield from the state level trials. It has recorded higher pod yield of 1632 kg/ha as compared to the checks viz., GG-2 (1255 kg/ha), GG-5 (1355 kg/ha) and GG-7 (1413 kg/ha). The genotype was also tested in Spanish bunch trials of AICRPG and performed better than GG-2 by 9.95% and 12.20% during kharif, 2007 and 2008, respectively with a mean increase of 11.00%. But, it was comparable with GG-7 and TG-37A. Average kernel yield of GJG-9 was 1183 kg/ha as against the checks viz., GG-2 (935 kg/ha), GG-5 (997 kg/ha) and GG-7 (1026 kg/ha). GJG-9 had recorded an average 100 kernel weight of 36.89 g, average 100 pod weight of 96.70 g and average shelling out-turn of 72.49%. The reaction against tikka, rust and collar rot, the variety was comparable to the check varieties under field conditions. However, GJG-9 was found tolerant to the stem rot as compared to the check varieties. Whereas, the damage due to thrips and jassids of GJG-9 was comparable to the check varieties. Based on the superior performance, GJG-9 has been released in 2010 for general cultivation in the kharif bunch groundnut growing areas of Gujarat State.